(untitled) - Alana Amoretta; Sumitro (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Purpose of this study: The research aims to analyze the character of Michael as a leader in the virtual and real world. The Coffin gives a real sensation during the game. Methods: This study used descriptive qualitative method. The writer applied postmodernist approach to analyze the hyperreality in the novel. It has been explained before that hyperreality comes as a result of postmodern era. The theory used is the theory of hyperreality by Jean Baudrillard along with the process of simulation and simulakra. Main findings: The results showed that the Coffin as an intermediary between the players against the game world is a simulation. The intermediary processes how reality and creation are blurred. Simulakra is the game itself. This virtual reality game is no longer a representation, but rather a duplicate without the original reference. Hyperreality is when Michael's character as a leader in the game world is brought into the real world. Michael could not distinguish between reality and artificial. Applications of this study: This study discusses how hyperreality is depicted in the novel The Eye of Minds by James Dashner. This novel tells the story of Michael who is addicted to virtual reality games. Michael prefers to spend time in Coffin, which is a sophisticated intermediary that connects the real world and the game. Novelty/ Originality of this study: Conclusion this research is everything that happens in the virtual reality game does not relate to any object in reality. .